Twelve tips for developing and running a successful women's group in international academic medicine. (2nd November 2019) - Ibrahim, Halah; Stadler, Dora J.; Archuleta, Sophia; Anglade, Pascale; Cofrancesco, Joseph
Abstract: Gender inequity in academic medicine remains an important issue worldwide. While institutional programs and policies can help promote equity in recruitment, retention, scholarship, promotion, and leadership, they often do not address the physical and social isolation that many women in international academic medicine face. Creating networking opportunities through building women's groups can provide a personal and professional support structure that decreases isolation and promotes the advancement of women. Based on a multidisciplinary literature review on change processes, group formation, and women's empowerment, as well as lessons learned from personal experience, we offer 12 tips to successfully create, maintain, and support physician women's groups, employing Kotter's change-management framework. We believe that these groups can provide a structured platform for networking opportunities to advance women physicians in academic medicine worldwide.